Efficacy and safety of hepatic arterial infusion chemotherapy combined with tyrosine kinase inhibitors and immune checkpoint inhibitors in the treatment of advanced hepatocellular carcinoma with portal vein tumor thrombosis in the main trunk - Liu, Qi; Zhang, Ying; Zhang, Jingwen; Chen, Luhao; Yang, Yi; Liu, Yan (Frontiers in Oncology, 2024)
Purpose To evaluate the efficacy and safety of mFOLFOX-based hepatic arterial infusion chemotherapy (HAIC) combined with tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) in the treatment of advanced hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT) Methods This retrospective study included patients who received mFOLFOX-based HAIC combined with TKIs and ICIs from January 2021 to January 2023. The primary outcome was the objective response rate of PVTT response, and the secondary outcomes were 6-month, 1-year survival rate, overall survival (OS), and corresponding adverse events and complications were also evaluated. PVTT responses were assessed using ITK-SNAP software. Results A total of 37 patients were included in the analysis, 18.92% achieved a complete response and 56.76% achieved a partial response in PVTT response. The objective response rate (ORR) of PVTT was 75.68%. The 6-month survival rate was 89%, the 1-year survival rate was 66%, and the median OS was 15.8 months. In univariate analysis, Child-Pugh score (P=0.010) was important factor for predicting OS; in multivariate analysis, Child-Pugh score (P=0.015, HR= 3.089, 95%CI: 1.250–7.633) was the important factor for predicting OS. In terms of adverse reactions, the most common adverse reactions associated with HAIC are pain and thrombocytopenia associated with oxaliplatin. Conclusion FOLFOX-based HAIC combined with TKIs and ICIs induced an objective response rate of 75.68% in PVTT. Clinical signicance FOLFOX-based HAIC combined with TKIs and ICIs provides more treatment options for PVTT.